BLOCKCHAIN IN EDUCATION: HOW TO MANAGE STUDENT CREDITS OF HIGHER EDUCATION THROUGH THE BLOCKCHAIN? - Kumalakov, B.A; Shakan Y. , Y. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Currently, technologies are developing very quickly and the need for information security is constantly increasing. In this connection, Blockchain technology is becoming in demand, which allows us to keep information safety and integrity. In addition, the technology enables the creation of a decentralized environment where transactions and data are take place without any third party organization. We proposed a decentralized web resource based on the Ethereum platform for managing student credits. The decentralized application (Dapp), will process, manage and control tokens, which represent credits that students gain for completed certain courses. The credit system is a first step towards a more transparent and technologically advanced form which could be used by universities and students to manage credits. The novelty of this scientific research is the creation of a web-based information resource based on Blockchain technology. Thanks to this resource, it becomes possible to track students’ grades and receive reliable information about higher education. This completely eliminates the possibility of making changes to existing records.